Systematic Review of Assessment Precision of CT Perfusion Imaging in Acute Ischemic Stroke - Susilo, Budi; Novita (International Medical Journal Corp. Ltd, 2024)
Background: CT perfusion (CTP) has emerged as a valuable tool in the management of acute stroke, providing essential quantitative information on the extent of the irreversibly injured ischemic core and the potentially salvageable ischemic penumbra. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: The optimal duration of a CTP scan relates to the arrival time and width of the contrast bolus of the scan. This knowledge can be used to optimize CTP scan protocols and to determine if a scan is of sufficient duration.